-3(1-5r)-8r=4r-36

Simple and best practice solution for -3(1-5r)-8r=4r-36 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(1-5r)-8r=4r-36 equation:


Simplifying
-3(1 + -5r) + -8r = 4r + -36
(1 * -3 + -5r * -3) + -8r = 4r + -36
(-3 + 15r) + -8r = 4r + -36

Combine like terms: 15r + -8r = 7r
-3 + 7r = 4r + -36

Reorder the terms:
-3 + 7r = -36 + 4r

Solving
-3 + 7r = -36 + 4r

Solving for variable 'r'.

Move all terms containing r to the left, all other terms to the right.

Add '-4r' to each side of the equation.
-3 + 7r + -4r = -36 + 4r + -4r

Combine like terms: 7r + -4r = 3r
-3 + 3r = -36 + 4r + -4r

Combine like terms: 4r + -4r = 0
-3 + 3r = -36 + 0
-3 + 3r = -36

Add '3' to each side of the equation.
-3 + 3 + 3r = -36 + 3

Combine like terms: -3 + 3 = 0
0 + 3r = -36 + 3
3r = -36 + 3

Combine like terms: -36 + 3 = -33
3r = -33

Divide each side by '3'.
r = -11

Simplifying
r = -11

See similar equations:

| x^2+11x+2=28 | | 6(-7-6x)=-78 | | 3x-5=2+3x-7 | | 7x-2(6x-3)=36 | | (5-2x)/(2x-4)=0 | | 7(1-1x)=7 | | -3(-5x+1)=-8 | | M(I-7)=0 | | 6(-8+4x)=-48 | | 192+8logx=160 | | 44x-4=26x+4 | | -5(5+3x)=-205 | | ((x^2)-8x-1)/(x-1) | | 4(x+3)=2x-11 | | 44=-5x-26 | | 400+50ln(90t+1)=.05(12300+1000ln(t+1)) | | -3(3x-9)=99 | | 16x=1.6 | | 3=y^2-2y-2 | | 7(2-7x)=-231 | | (x+5)-2(3+5)-5x=13+4(x-1) | | -5=5n+6n-n | | 5.28+7.1x=-0.41(1+2)-6.3x | | 3.5n+6.4=4.25 | | 4y+24=5y+40 | | 8y-20=120 | | 2x-12=30+x | | 2x-51=99 | | 4y^2=7t+15 | | 6x-10y-25=0 | | 4(1x+7)=64 | | 11z+2=19z-2 |

Equations solver categories